Metode Memahami Sumber Ajaran Islam - Anggi Kusumah Wildani; Syafa'atun Nahriyah (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2021)
Islam as a religion that applies eternally and applies to all mankind has a complete source as well. The source of Islamic teachings is the Qur'an and Sunnah which are very complete. The question that will arise is what methods are used to understand the Qur'an and Sunnah as a source of Islamic teachings. As it is known that the AI-Qur'an is a source of teachings that are basic and global in nature, while many explanations are explained and complemented by the Sunnah. But, in accordance with the times, many new problems arise about how to understand the AI-Qur'an and Sunnah. In these new problems, of course, the answer is to what extent Islam explicitly defines and solves them. Thus, the methodology of Islamic teaching sources is needed as a method in explaining an issue of the Al-Qur'an and Sunnah. There are several methodologies, namely the ulumul tafsir methodology, the ulumul hadith methodology, the philosophical and theological methodology (kalam), the mystic and mystical methodology of Islam, the methodology of the study of fiqh and the rules of ushuliyah.